Impact of maternal vitamin D status during pregnancy on the prevalence of neonatal vitamin D deficiency - Yasser F. Aly; Mohamed A. El Koumi; Rehab N. Abd El Rahman (MDPI AG, 2013)
Maternal vitamin D deficiency is not uncommon. The lack of vitamin D during pregnancy may result in poor fetal growth and altered neonatal development that may persist into later life. Recognition of risk factors and early detection of vitamin D deficiency during pregnancy is important in order to prevent neonatal vitamin D deficiency and related complications. The aim of the current study is to assess the effect of maternal vitamin D status on the neonatal vitamin D stores. A total of 92 pregnant women at the end of the 3rd trimester and their newborns were recruited from Al Khafji Joint Operation Hospital, Saudi Arabia, during the year 2011. Maternal and cord blood samples were taken for determination of serum levels of circulating 25-hydroxyvitamin D3 [25(OH)D3] concentration, serum calcium (Ca++), phosphorus (PO4) and alkaline phosphatase (ALP). Compared with pregnant women with adequate vitamin D levels, women deficient in vitamin D had infants with vitamin D deficiency (X±SD 33.44±18.33 nmol/L vs 55.39±17.37 nmol/L, P=0.01). Maternal and neonatal serum 25(OH)D3 levels showed a positive correlation with serum Ca++ and negative correlation with serum PO4 and ALP. Neonatal 25(OH)D was related to maternal 3rd trimester levels (r=0.89, P=0.01). The newborn serum 25(OH)D3 concentrations rely on maternal vitamin D status. Poor maternal vitamin D status may adversely affect neonatal vitamin D status and, consequently, calcium homeostasis.